Reformasi Penyajian Laporan Keuangan Syariah: Kesiapan Bank Umum Syariah Menghadapi PSAK 401 (Revisi 2025) dan Implikasinya terhadap Kualitas serta Komparabilitas Pelaporan - Fitri Yani; Yusnita Yusnita (Universitas Methodist Indonesia, 2026)
The Indonesian Sharia Accounting Standards Board ratified PSAK 401 (Revised 2025) on the Presentation and Disclosure in Sharia Financial Statements on 21 October 2025, effective for annual periods beginning on or after 1 January 2027. Because no Islamic commercial bank (Bank Umum Syariah/BUS) has yet reported under the new standard, this study is an ex ante readiness assessment rather than an ex post impact evaluation. Using content analysis of the 2025 annual reports of ten BUS and a comparative normative analysis of the standard texts, the study applies a nine-indicator readiness rubric scored on a three-point ordinal scale. The aggregate readiness index reaches 67.8 per cent, ranging from 61.1 to 77.8 per cent. Readiness is uneven rather than uniformly low: banks already satisfy the operating-result subtotal, the notes structure, and the zakat and benevolence fund statements, but none classifies income and expenses into the investing and financing categories, none discloses its own management-defined performance measures, and only six of ten acknowledge the forthcoming standard at all. The findings indicate that the binding constraint is not the volume of disclosure but the architecture of the income statement, and that comparability gains will depend on uniform technical application rather than on the issuance of the standard itself. The Indonesian Sharia Accounting Standards Board ratified PSAK 401 (Revised 2025) on the Presentation and Disclosure in Sharia Financial Statements on 21 October 2025, effective for annual periods beginning on or after 1 January 2027. Because no Islamic commercial bank (Bank Umum Syariah/BUS) has yet reported under the new standard, this study is an ex ante readiness assessment rather than an ex post impact evaluation. Using content analysis of the 2025 annual reports of ten BUS and a comparative normative analysis of the standard texts, the study applies a nine-indicator readiness rubric scored on a three-point ordinal scale. The aggregate readiness index reaches 67.8 per cent, ranging from 61.1 to 77.8 per cent. Readiness is uneven rather than uniformly low: banks already satisfy the operating-result subtotal, the notes structure, and the zakat and benevolence fund statements, but none classifies income and expenses into the investing and financing categories, none discloses its own management-defined performance measures, and only six of ten acknowledge the forthcoming standard at all. The findings indicate that the binding constraint is not the volume of disclosure but the architecture of the income statement, and that comparability gains will depend on uniform technical application rather than on the issuance of the standard itself.